Réponses

Meilleure réponse !
2013-03-08T20:36:35+01:00

a = 1 +4x = x-3

a = 4x-x = -3-1

a = 3x = -4

   x = -4/3

 

b) 3x+7 = 5(x+1)

     3x +7 = 5x +5

    3x -5x = 5-7

    -2x = -2

     x = 1

 

c) 2(x-1) = 3(2+x)

 

2x-2 = 6 +3x

2x-3x = 6+2

-x = 8

d) (x-4)(x-1) = 0

soit x-4 = 0 donc x = 4

soit x-1  = 0 alors x = 1

 

e) (2x-1)(x+2) = 0

soit 2x-1 = 0 donc 2x= 1 et x = 1/2

soit x+2 = 0 alors x = -2

f) (3x+4)+(2-4x ) = 0

3x+4+2-4x = 0

-x+6 = 0

-x = -6

x = 6

2013-03-08T20:38:29+01:00

a) 1+4x = x-3

    +4x -x = -1 -3

      +3x = -4

          x = -4/3

b) 3x +7 = 5(x+1)

   3x +7 = 5x +5

    3x -5x = -7 +5

    -2x = -2

       x = -2/2 = +1

c) 2x -2 = 6 +3x

    2x -3x = +2 +6

    -x = 8

     x = -8

d) x-4=0 x= 4

x-1 = 0  x = 2   

e) 2x-1 = 0 --------     2x = 1-------------- x = 1/2

x+2=0 x = -2

f) 3x+4=0

3x = -4

x= -4/3

2-4x = 0

-4x = -2

x = -2/4 = -1/2

 

f)